DINAMIKA KOMUNIKASI ANTARPRIBADI DALAM MEMBANGUN SOLIDARITAS KOMUNITAS COSPLAYER BENGKULU: KAJIAN FENOMENOLOGI BERBASIS TEORI DE VITO - Hafis Al Yusufi; Riswanto (Jurnal MADIA (Jurnal Humas dan Media Kontemporer), 2026)
This study examines the role of interpersonal communication in strengthening solidarity within the Bengkulu Cosplayer communityan interestbased community predominantly composed of introverted individuals. Using a qualitative phenomenological approach, data were collected through indepth interviews, participant observation, and documentation involving five purposively selected informants at Bencoolen Mall, Bengkulu (1–8 December 2025). Data analysis followed Miles and Huberman's interactive model, validated through source and technique triangulation. Findings show that all five elements of De Vito's interpersonal communication theoryopenness, empathy, supportiveness, positiveness, and equalitymanifested concretely and worked synergistically to construct organic solidarity. Openness developed gradually, facilitated by WhatsApp and Discord. Empathy grew from shared experiences of social stigma. Support manifested across practical, emotional, and informational dimensions through a sustained payingitforward culture. Positiveness was built through genuine appreciation of every member's contribution. Equality was practiced through a onepersononevote principle. The resulting solidarity is organic, built not merely from shared interests, but from relationship quality consistently cultivated through effective interpersonal communication. Keywords: Cosplayer Community, De Vito's Theory, Interpersonal Communication, Phenomenology, Solidarity